(untitled) (Research, Society and Development, 2022)
Hypertensive crisis is a significant clinical entity with considerable mortality and morbidity, with organ damage in many patients, a factor that significantly hinders quality of life. In view of this, the importance of urgent and emergency care plan in situations of hypertensive crisis is highlighted, in order to ensure immediate care that can offer a rapid and gradual reduction in blood pressure levels. The objective of the study was to offer a brief narrative review on the approach of the hypertensive crisis in the face of the terminologies ’hypertensive urgency’ and ’hypertensive emergency’, in order to understand the clinical aspects and the main conducts performed in the care, articulating with the performance of the professional nurse facing this clinical condition. This research was elaborated from a bibliographic survey in the scientific databases of the Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature on Health Sciences (LILACS), Google Scholar and Virtual Health Library (VHL), with publications between 2015 and 2020 as a temporal delimitation. In view of the results obtained, it was found that all articles presented an approach to hypertensive crisis in urgency and emergency services. Noting that both hypertensive crisis terminologies are used, as well as the terms ’hypertensive urgency’ and ’hypertensive emergency,’ to present the peculiarities and relevant results about each condition. It is also important to highlight the need for better care by the nursing team, mainly because they deal directly and frequently with patients, using risk classification as an essential tool in redirecting the flow of care in urgent and emergency services. The demands of hypertensive crisis in the urgency and emergency sector signal the need to improve local health promotion and prevention actions, with primary health care playing a fundamental role in the development of these strategies.